THE TRAGIC ELEMENTS IN BRAD SILBERLING'S (2004) LEMONY SNICKET'S A SERIES OF UNFORTUNATE EVENTS - Marcellina Ariska P.N.; G.M. Adhyanggono (Celt: A Journal of Culture, English Language Teaching & Literature, 2013)
Movie is a kind of literary works in addition to novels, poems or songs. There are some genres of movie; one of them is comedy. Black comedy is its sub-genre. Lemony Snicket's A Series of Unfortunate Events is a black comedy movie which includes hamartia, anagnorisis, peripeteia, and catharsis. They are the key elements of Aristotle's theory of tragedy. In this paper, the writer shows the existence of those key elements in the movie. Also, the writer explains the extent of tragic elements in affecting the story of this movie. This paper shows that from the perspective of Aristotle's theory of tragedy, Lemony Snicket's A Series of Unfortunate Events can be viewed as tragedy.